National Legal Frameworks and International Challenges of Netflix Regulation: Censorship, Taxation, Cross-Border Licensing - Bambang Priyatna Kusuma; Chelsea Shine Efendy; Cornelia Editha Santoso (Pena Justisia: Media Komunikasi dan Kajian Hukum, 2025)
This study examines the regulatory challenges surrounding Over-The-Top (OTT) platforms such as Netflix within the context of Indonesian law and global regulatory comparisons. Indonesia’s national content censorship system, managed by the Film Censorship Board and the Ministry of Communication and Informatics, continues to apply a preventive and normative pre-censorship paradigm. This approach creates tension with the principle of self-regulation implemented globally by Netflix, resulting in legal uncertainty and limited content access for Indonesian users. In the fiscal domain, the implementation of Value Added Tax (VAT) on foreign digital services aims to ensure tax fairness, yet the application of Personal Income Tax (PIT) remains problematic due to the absence of physical presence (Permanent Establishment) and the non-implementation of the Significant Economic Presence (SEP) concept. Meanwhile, issues related to cross-border licensing highlight the complexity of copyright protection and cross-border content distribution. Indonesia continues to emphasize territorial restrictions in line with the Berne Convention and lacks regional harmonization similar to the European Union’s Audiovisual Media Services Directive (AVMSD). This study concludes that Indonesia needs to develop co-regulation mechanisms and strengthen an adaptive digital legal framework to safeguard cultural values without hindering freedom of expression or the competitiveness of the national digital economy.